2021
DOI: 10.7717/peerj.11037
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression and its impact on quality of life in frontline otorhinolaryngology nurses during the COVID-19 pandemic in China

Abstract: Objective Exposure to the coronavirus disease 2019 (COVID-19) was associated with high risk of mental health problems among frontline nurses. This study examined the prevalence of depressive symptoms (depression hereafter) and its impact on quality of life (QOL) in otorhinolaryngology (ENT) nurses during the COVID-19 pandemic in China. Methods An online study was conducted between March 15 and March 20, 2020. Depression and QOL were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…WeChat is a well-established social media in China with over a billion active users. Wenjuanxing is a WeChat-based online survey platform widely applied in survey studies [ 26 , 27 ]. During the time this study was conducted, a significant portion of the students was taking online classes either in their home country or in the US.…”
Section: Methodsmentioning
confidence: 99%
“…WeChat is a well-established social media in China with over a billion active users. Wenjuanxing is a WeChat-based online survey platform widely applied in survey studies [ 26 , 27 ]. During the time this study was conducted, a significant portion of the students was taking online classes either in their home country or in the US.…”
Section: Methodsmentioning
confidence: 99%
“…Nurses experience bad moods, regrets, fears, and sadness while treating Covid-19 patient and distributing duties in China (He et al, 2020). Furthermore, Tian et al, (2021) confirmed that nurse depression could impact the quality of life of nurses and the quality of nursing care provided (Tian et al, 2021). Health education interventions were directed towards vulnerable population, who may be at increased risk of contracting COVID-19.…”
Section: Lessons For Nursesmentioning
confidence: 84%
“…Its validity has been tested in Chinese populations [33,34]. The degree of insomnia is assessed by the final score, which is divided into 4 score ranges corresponding with levels of insomnia severity: not clinically significant (0-7), subthreshold (8)(9)(10)(11)(12)(13)(14), moderate severity clinical (15)(16)(17)(18)(19)(20)(21), and severe clinical (22)(23)(24)(25)(26)(27)(28) insomnia [35]. Generally, a higher score on ISI indicates a higher severitiy of insomnia.…”
Section: Methodsmentioning
confidence: 99%